A Study to Assess the Knowledge on Perception and Health Care Seeking Behavior Regarding Neonatal Danger Signs among Postnatal Mothers in Selected Hospital at Bijapur, with a View to Develop Information Booklet - Hiremath, Shridevi (Indian Journal of Nursing Sciences, 2024)
Aim: The aim of this study was to evaluate the knowledge on perception and health care seeking behavior regarding neonatal danger signs (NDSs) among postnatal mothers. Materials and Methods: A descriptive survey design was used for the study. The study was conducted at Government Hospital, Bijapur. The sample comprised 60 postnatal mothers of selected Government Hospital, Bijapur. Sample was selected using non-probability, convenient sampling technique. Data were collected using a structured knowledge questioner. Data were analyzed using descriptive and inferential statistics. Results: The result of this study showed that the pre-test majority of the respondents of the percentage of knowledge scores in general information about NDSs was 38.88.5%, causes of danger signs were 41%, signs and symptoms of danger signs were 41.66%, prevention of danger signs was 49.44%, and management of NDSs was 46.19%, it shows the administration of information booklet. The pre-test, majority of subjects 31 (51.66%) had average knowledge, 17 (28.33%) had good knowledge, and 12 (20%) had poor knowledge. The calculated Chi-square value was less than the table value and P > 0.05; hence, there was no significant association between pre-test knowledge score and selected sociodemographic variables. It shows that there was significant association between the gain in knowledge scores and selected demographic variable. Conclusion: The findings of the study concluded that the majority of subject had average knowledge on perception and health care seeking behavior regarding NDSs among postnatal mothers